Estudo sobre a alimentação das raias de água doce Potamotrygon orbignyi, Potamotrygon scobina e Plesiotrygon iwamae (Chondrichthyes: Potamotrygonidae) na baía de Marajó-Pará - Bragança, Alexandre José M. (Museu Paraense Emílio Goeldi, 2023)
South America has a large number of freshwater ray species. These rays are distributed throughout the Amazon basin and belong to the Potamotrygonidae family. A feeding study of the species Potamotrygon scobina, Potamotrygon orbignyi and Plesiotrygon iwamae was carried out with material collected in May, August and October 2000 from Cotijuba Island, in the Amazonian estuary. The stomach contents of 40 specimens of Potamotrygon orbignyi, eight depotamotrygon scobina and four of Plesiotrygon iwamae were analyzed. During the stomach content analyses, the food items were identified down to the lowest possible taxonomic category and for each item the measurements of: Frequency of Occurrence (%F.O.), Numerical (%N), Weight (%P), Relative Importance Index (IRI) and respective percentage (%IRI), Level of Repletion and Degree of Digestion. The results obtained (%IRI) indicated that the rays of the species P. orbignyi feed preferentially on water lice (Family Sphaeromatidae - 67%) and insect larvae (Family Chironomidae - 32%). The rays of the species P. scobina fed on water lice (Family Sphaeromatidae - 80%) and shrimps (Family Palaemonidae - 18%); while the rays of the species P. iwamae fed predominantly on shrimps (Family Palaemonidae - 88%). The level of repletion and degree of digestion indicated, respectively, that most stomachs were filled with food content up to half (50%) and that food items were mostly poorly digested in the specimens of all three species. The results indicated that these rays show a feeding preference for crustaceans and probably fed shortly before capture.